Aqueous extract of pomegranate enriched in ellagitannins prevents anxiety-like behavior and metabolic changes induced by cafeteria diet in an animal model of menopause. (December 2020) - Estrada-Camarena, E.M.; López-Rubalcava, C.; Ramírez-Rodríguez, G.B.; Pulido, D.; Cervantes-Anaya, N.; Azpilcueta-Morales, G.; Granados-Juárez, A.; Vega-Rivera, N.M.; Islas-Preciado, D.; Treviño, S.; de Gortari, P.; González-Trujano, M.E.; et al.
Abstract: Women around menopause are vulnerable to present psychiatric and metabolic disorders; thus, therapies that contribute to treat both pathologies are required. Previous reports showed that an aqueous extract of pomegranate (Punica granatum), enriched in ellagitannins, exerts an antidepressant-like effect in ovariectomized rats. We analyze whether this aqueous extract of P. granatum (AE-PG) prevents the anxiety-like behavior induced by a cafeteria diet (CAF) in middle-aged ovariectomized rats at the same time that it prevents an increase in body weight, glucose, lipids, and the changes on mRNA expression of the peroxisome proliferator-activated receptor-gamma (PPAR-γ) in the liver. Also, the effects of AE-PG on the protein levels of PPAR-γphospho-PPAR-γ, extracellular signal-regulated protein kinase (ERK1/2) and phospho-ERK1/2 were measured in the hippocampus and amygdala. CAF induced anxiety-like behavior, augmented lipids and glucose blood levels, body weight, visceral fat, insulin resistance, and decreased mRNA expression of PPAR-γ in the liver. In rats fed with the CAF, AE-PG prevented the anxiety-like behavior, reduced body weight, lowered lipid levels, reduced insulin resistance, and increased PPAR-γ mRNA expression in the liver. In the hippocampus, ERK1/2 but not PPAR-γ protein levels were decreased by CAF, while AE-PG prevented these effects. In the amygdala, CAF increased the phosphorylation of PPARγ, and AE-PG prevented it. In contrast, AE-PG rescued the decreased ERK1/2 protein level in the hippocampus caused by CAF. In conclusion, AE-PG treatment prevented anxiogenic and metabolic effects induced by CAF, and its effects appear to be mediated by ERK1/2 and PPARγ depending on the brain area studied. Highlights: Cafeteria diet (CFD) induced anxiety-like behavior and metabolic alterations in a menopause model. Aqueous extract of Punica granatum (AE-PG) prevented anxiety-like behavior induced by the CFD. AE-PG decreased insulin resistance, lipids, and abdominal perimeter. CFD and AE-PG modulated PPARγ receptor activation mainly in the amygdala. AE-PG rescued the decreased ERK1/2 protein level in the hippocampus caused by CAF.